Метод оценивания изменяющихся во времени параметров регрессионных моделей - Корхин, А.С. (Проблемы управления и информатики, 2012)
В основу описаного методу покладенo двокритеріальну задачу оцінювання змінних параметрів лінійної регресії. Вона дозволяє одержати оцінки параметрів, використовуючи достатньо обмежену апріорну інформацію. Вивчено властивості отриманих оцінок. Наведено результати машинного експерименту, які показали працездатність запропонованого методу. The two-criterion problem of evaluation of linear regression variable parameters is a basis of the described method. It allows one to get estimations of parameters using limited enough a priori information. Properties of the obtained estimations are studied. The results of machine experiment, which showed the efficiency of the offered method are given.